Strategi Pemasaran Daging Se’i Babi di Kabupaten Kupang : (Studi Kasus Se’i Babi Baun) - Namah, Sindi Alvian; Krova, Maria; Lalus, Matheos (Animal Agricultura, 2024)
The purpose of this study to find out how the marketing strategy of se'i pork in Baun, Kupang Regency. The method used in this research is an in-depth study, to obtain primary data and secondary data through observation, interview, and documentation techniques. The data was analyzed using the IFE, EFE, SWOT and QSPM matrix methods. Based on the IFE matrix analysis, the total value of X = 1.15 is obtained, while in the EFE matrix the value of Y = 1.27. The position of the SWOT quadrant of the Baun pork se'i business is in quadrant 1, the SWOT matrix of the Baun pork se'i business obtained seven strategies that can be implemented by entrepreneurs, namely 1). Increase promotional activities through social media, 2). Maintaining product quality, 3). Improve technology and business management, 4). Expanding market segmentation and increasing consumer loyalty, 5). Retaining potential customers, 6). Collaboration with other parties, 7). Product diversification. And obtained a total QSPM matrix value of 36.84. Therefore, Baun pork se'i entrepreneurs can add business branches in various places to make it easier for consumers to get these products.